Genetic parameters and productivity of quinoa in western Paraná - Vasconcelos, Edmar Soares de; Hoepers, Lívia Maria Lemos; Amaral, Rafaela Goularte; Egewarth, Vanessa Aline; Strenske, Andressa (Acta Scientiarum. Agronomy, 2016)
Quinoa has been gaining attention because of its nutritional quality, low cholesterol and lack of gluten; in Brazil, the cultivation efforts in the different regions are mainly related to breeding. This study aimed to determine the genetic parameters and evaluate the productivity of the different genotypes of quinoa for detecting genotypes amenable to selection. The experiment was conducted in crop years 2010/11 and 2011/12 in environment 1 and environment 2, respectively. In environment 1, the evaluation of 61 genotypes was performed, and in environment 2, 31 genotypes were evaluated. The experimental design was a randomized block with two replications; each plot measured 2.0 x 5.0 m (10 m²) and consisted of four rows spaced at 0.45 m. Data collected on the productivity, plant height at maturation and growth cycle were analyzed using an analysis of variance, average tests and estimates of the genetic parameters. The genotypes N24 and N08 were the only genotypes more productive than the other 46 genotypes, with values of productivity of 1446.23 and 1428.93 kg ha-1 and with a growth cycle of 117 and 111 days, respectively. The heritability values determined demonstrate the possibility of genetic gain using joint selection that involves two environments.